Personal space and other stories - Santos, Chit Roces (Teresita Roces) 1940- (Mandaluyong City Published and exclusively distributed by Anvil Publishing, Inc., 2013)
Personal essays on various aspects of the author's life.
The good life -- Answering machine -- The forest and the mayor -- This must be love -- The dye is cast -- Determined dyer -- Tres Marias de Arrocerros -- Losing bebe -- Good sex, bad sex -- Without mom -- My old man -- Everybody loves Gilda -- Suddenly, Mona -- Grandma love -- The educated heart -- Arrocerros rise again -- Managing anger and grief -- Beating buffets -- Foreign factor -- Older woman -- Mother love -- My life as a musical -- Belabeled -- Personal Space -- Reading love -- Delicadeza -- Rules of Estrangement -- Coming of age -- Autumn years -- In the presence of art -- Delusions of entitlement -- And then there were four -- Where I'm at -- Moment of truth -- Dress and deportment -- Desperate dyer -- Senior bride -- Thinking of gym -- I believe.
Keywords: Philippine essays (English)